The Viceroys of Ireland - Kingston, Charles, 1884-1944 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Viceroys of Ireland" by Charles Kingston O'Mahony is a historical account written in the early 20th century. The book delves into the long and complex history of the viceroys who ruled Ireland, detailing their stories and the impact of their governance on Irish society over a period of more than seven hundred years. This comprehensive account seeks to provide readers with insights into the political dynamics between the English crown and the various Irish factions. At the start of this historical narrative, the author introduces the conquest of Ireland by Henry II. The opening chapters focus on the initial attempts at control over the island, recounting battles and the harsh realities faced by the early English rulers, including viceroys such as Hugh de Lacy. O'Mahony emphasizes the fierce resistance of the Irish people and the frequent failures of the English to assert their authority, setting the tone for the struggles that define the relations between Ireland and England throughout history. The text addresses themes of betrayal, power, and the complexities of colonial governance, laying the foundation for a deeper exploration of individual viceroyalties that follow. (This is an automatically generated summary.)
Release date is 2011-05-22
Produced by Al Haines
Keywords: Ireland -- History; Ireland -- Politics and government; Ireland -- Biography